Effect of temperature and solvent properties on the process of complex formation between crown ether 15C5 and Na+ in the (propan-1-ol + water) mixture at temperatures from T = 293.15 K to T = 308.15 K. (October 2017) - Jóźwiak, Małgorzata; Madej-Kiełbik, Longina; Wasiak, Michał; Jóźwiak, Andrzej
Highlights: The system 15C5/Na + complex + water + propan-1-ol have been investigated. The thermodynamic functions of 15C5/Na + complex formation were calculated. The enthalpy of complex formation has been calculated using calorimetric method. The enthalpy of complex formation has been calculated from van't Hoff's equation. The obtained results have been compared. Abstract: Thermodynamic functions of complex formation of 15-crown-5 ether (15C5) with sodium cation (Na + ) in the mixtures of propan-1-ol (PrOH) with water (W) at different temperatures have been calculated. To obtain this function two experimental methods have been used. The equilibrium constants of complex formation (15C5/Na + ) have been determined by conductivity measurements and the enthalpic effect of complex formation has been measured by the calorimetric method and has been also calculated using van't Hoff's equation. The complexes are enthalpy stabilized but entropy destabilized. Effect of solvent properties on the process of complex 15C5/Na + formation in PrOH + W mixtures has been discussed. The obtained results were compared with analogous data in the mixtures of water with methanol or ethanol and discussed.